Hypoxia-Induced Intracellular and Extracellular Heat Shock Protein gp96 Increases Paclitaxel-Resistance and Facilitates Immune Evasion in Breast Cancer - Tian, Tian; Han, Jiguang; Huang, Jian; Li, Shangziyan; Pang, Hui (Frontiers in Oncology, 2021)
Backgrounds: Hypoxia contributes to cancer progression, drug resistance and immune evasion in various cancers, including breast cancer (BC), but the molecular mechanisms have not been fully studied. Thus, the present study aimed to investigate this issue. Methods: The paclitaxel-sensitive BC (PS-BC) cells were administered with continuous low-dose paclitaxel treatment to establish paclitaxel-resistant BC (PR-BC) cells. Exosomes were isolated/purified by using the commercial kit, which were observed by Transmission electron microscopy (TEM). Cell viability was measured by MTT assay, cell apoptosis was determined by flow cytometer (FCM). Gene expressions were respectively measured by Real-Time qPCR, Western Blot and immunofluorescence staining assay. The peripheral mononuclear cells (PBMCs) derived CD8+ T cells were obtained and co-cultured with gp96-containing exosomes, and cell proliferation was evaluated by EdU assay. ELISA was employed to measure cytokine secretion in CD8+ T cells’ supernatants. Results: HSP gp96 was significantly upregulated in the cancer tissues and plasma exosomes collected from BC patients with paclitaxel-resistant properties. Also, continuous low-dose paclitaxel treatment increased gp96 levels in the descendent PR-BC cells and their exosomes, in contrast with the parental PS-BC cells. Upregulation of gp96 increased paclitaxel-resistance in PS-BC cells via degrading p53, while gp96 silence sensitized PR-BC cells to paclitaxel treatments. Moreover, PR-BC derived gp96 exosomes promoted paclitaxel-resistance in PS-BC cells and induced pyroptotic cell death in the CD8+ T cells isolated from human peripheral blood mononuclear cells (pPBMCs). Furthermore, we noticed that hypoxia promoted gp96 generation and secretion through upregulating hypoxia-inducible factor 1 (HIF-1), and hypoxia increased paclitaxel-resistance and accelerated epithelial-mesenchymal transition (EMT) in PS-BC cells. Conclusions: Hypoxia induced upregulation of intracellular and extracellular gp96, which further degraded p53 to increase paclitaxel-sensitivity in BC cells and activated cell pyroptosis in CD8+ T cells to impair immune surveillance.